EVALUASI PRESTASI KERJA PERUSAHAAN DENGAN METODE ANALISIS RASIO LAPORAN ARUS KAS PADA PT. INDOSAT TBK. - Hayatie, Marliza Noor; Machfiroh, Ines Saraswati (Jurnal Ecoment Global, 2021)
Cash flow information is a method used in order to find out about the development of the company so that managers and shareholders can make the right policies for the company. The ratio of cash flow information is one of the financial performances analyzes that use a cash flow statement. The purpose of this study was to determine the analysis of cash flow statement information in assessing financial performance at PT. Indosat, Tbk. during 2016-2018. This study used descriptive qualitative method. The results showed that the financial performance of PT. Indosat, Tbk shows that the company's financial condition is not good because of the five ratios that are taken into account in assessing financial performance, only the ratio of cash to interest coverage illustrates an increase in financial performance. However, the overall financial performance of the company shows a decreasing trend every year.Â Keywords: Financial Statements, Cash Flow